Påvisande av Helicobacter spp hos hund : en metodologisk studie - Nicol, Claire (SLU/Dept. of Animal Environment and Health (until 231231), 2007)
The purpose of this study was to develop a reliable molecular-genetic method to determine the different species of helicobacter in dogs. The study is part of a larger project to map the prevalence of Helicobacter spp in healthy and sick dogs in Sweden, and to determine the possible connection of Helicobacter spp infection with gastrointestinal diseases in dogs.